2010
DOI: 10.2527/jas.2010-3214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutrient restriction of bovine dams during early gestation on postnatal growth and regulation of plasma glucose1

Abstract: Angus x Hereford heifers (15 mo and AI to a single sire) were used to evaluate the effect of prenatal nutritional restriction on postnatal growth and regulation of glucose in plasma. Dams (d 32 of gestation) were stratified by BW and BCS and allotted to low [LN, 55% of NRC (1996) requirements, n = 7] or moderate nutrition [MN, 100% of NRC (1996) requirements, n = 7]. After 83 d of feeding, dams were commingled and received a diet in excess of requirements. Dams were allowed to calve naturally, and bull calves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…In our experiment, the lack of differences in glucose concentrations throughout rearing between CONTROL and SUBNUT heifers indicated that glucose metabolism was not affected in their postnatal lives. Similarly, other studies have described no effect of nutritional restriction during early pregnancy on calf basal glucose concentration [11]. Regarding the breed, the higher glucose concentration at AI in PA than in PI could suggest that PA could have consumed more hay and straw (which were offered ad libitum, unlike the concentrate) than PI.…”
Section: Heifer Metabolic and Endocrine Profilesmentioning
confidence: 80%
See 1 more Smart Citation
“…In our experiment, the lack of differences in glucose concentrations throughout rearing between CONTROL and SUBNUT heifers indicated that glucose metabolism was not affected in their postnatal lives. Similarly, other studies have described no effect of nutritional restriction during early pregnancy on calf basal glucose concentration [11]. Regarding the breed, the higher glucose concentration at AI in PA than in PI could suggest that PA could have consumed more hay and straw (which were offered ad libitum, unlike the concentrate) than PI.…”
Section: Heifer Metabolic and Endocrine Profilesmentioning
confidence: 80%
“…However, the impact of gestational undernutrition, either in early, mid or late gestation, on the reproductive performance of the progeny is not fully understood. Several studies reported negative effects on reproductive traits of the female offspring, with lower antral follicle counts [9], impaired ovulation rate [10] or decreased fertility [10,11]. In contrast, other studies described equal [12] or higher [13] numbers of antral follicles and higher ovulation rate [13] in females from nutrient-restricted dams.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in this study, the increased insulin level exhibited by NR heifers is accompanied by an increase in BCS. Intrauterine growth restriction induced by a variety of maternal models such as glucocorticoid exposure (Long, Shasa, Ford, & Nathanielsz, ), obesity (Ford et al., ; Long, George et al., ) and nutrient restriction (Matveyenko, Singh, Shin, Georgia, & Devaskar, ) has been shown to alter offspring pancreatic and β‐cell function resulting in increased insulin secretion. Our data coincide with these findings as NR heifers show an increase in insulin concentrations during both the feeding trial and IVGTT suggesting altered pancreatic and β‐cell function.…”
Section: Discussionmentioning
confidence: 99%
“…After 10 weeks of feed intake monitoring, 21 heifers (7 per treatment group) were randomly chosen (via a random number generator) for intravenous glucose tolerance testing (IVGTT) using methods described by Long, Prado‐Cooper, Krehbiel, and Wettemann () with modifications. Heifers were removed from feed 18 hr before IVGTT, but were still allowed access to water.…”
Section: Methodsmentioning
confidence: 99%
“…A disproportionately large calf is the major contributor to dystocia in heifers 24,25 with calf birthweight 28 and heifer size 15 considered the primary factors causing this fetal- 1 feto-placental unit responds to nutrient intake, 1a: Epigene c changes in feto-placental genes in response to nutri on; 2 blood flow to the placenta and transporter changes affect placental permeability and func on 2a Gesta onal diet alters colostrum quality (Igs) and quan ty; 3 Plancental hormonal output modulates fetal environment. As illustrated in Table 1, the timing of dietary interventions impacts the observed effect upon birthweight: Interventions imposed prior to 100 days post-conception (dpc), although causing greater effects upon fetal organ development 34 , generally result in similar birthweights at term 35,36 . Nutrient restriction during the second trimester, however, may have the greatest influence on calf birthweight 30 2,37 sufficient to influence dystocia and thereby survival in the neonate.…”
Section: Birthweight Dystocia and Neonatal Survivalmentioning
confidence: 99%